Study on Awareness Policies for Dissemination of Family Internet Rules by Libertarian-Paternalism - Nagayuki Saito (International Telecommunications Society (ITS), 2018)
In order to discuss the future direction of policy making for protecting children online, this paper discusses the effectiveness of protection policies based on libertarian paternalism from the standpoint of behavioral economics by referring to the efforts of the Kariya authorities, Aichi Prefecture. In particular, this paper discusses the effects of setting a default rule as a countermeasure to the human heuristic decision making process with a fear that making irrational decisions causes parents and children to adopt a passive stance towards policy. This paper specifically analyzes whether the efforts functioned as libertarian paternalism and the cut-off time of "9pm" was reasonable for parents as a default time. Furthermore, in the case where child protection has been carried out from the perspective of paternalism, this study considers whether children and parents adjust their behavior.
Keywords: 330; Internet; Mobile Phone; Youth Protection Policies; Behavioral Economics; Libertarian Paternalism